SPEAKING UNDER COMMAND: FORMATIVE ASSESSMENT PRACTICES FOR CADET ENGLISH TRAINING (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Formative assessment, cadet training, English speaking skills, military communication, oral proficiency, feedback, command language.